EFFECT OF MODERATE STATIC MAGNETIC FIELD ON HUMAN BONE MARROW MESENCHYMAL STEM CELLS: A PRELIMINARY STUDY FOR REGENERATIVE MEDICINE - Molo, Kaya; Ordu, Emel (TRAKYA UNIV BALKAN YERLESESI ENSTITULER BINASI, 2021)
Static Magnetic Field (SMF) is one of the biophysiological stimulants which modulates physiological processes in different cell lines. Mesenchymal stem cells (MSCs) are important biological tools for regenerative medicine. Although it is known that SMFs cause a change in cellular membrane polarization, oxidative product concentrations, gene expression patterns and cell propagation rates, depending on exposure time and intensity, their effects on MSCs have not been properly explained yet. In this study, MSCs derived from human bone marrow were treated with moderate 328 mT SMF by using cylindric Neodymium Iron Boron (Nd2Fe14B) magnets to investigate its influence on orientation, proliferation rates and morphologies. Results showed that the treated cells gained more homogenous orientation than the non-treated cells, however SMF influence did not significantly change proliferation rates. The cells were grown under both chemically osteogenic induction and SMF to observe the osteogenic differentiation and biomineralization. Alkaline phosphatase (ALP) activity decreased significantly in the cells treated with SMF compared to the control groups. Alizarin Red S staining showed that mineralization also decreased in the cells. The results showed that an easily produced moderate SMF can be a useful physical stimulant to control the fate of MSC both in vitro and in vivo.
Keywords: ORIENTATION; Science & Technology - Other Topics